Efektivitas Komunikasi Iklan Televisi dan Pengaruhnya terhadap Pembelian Produk Perikanan oleh Ibu Rumah Tangga di Kelurahan Lubang Buaya, Kecamatan Cipayung, Jakarta Timur - Popong Nurhayati; Trukan Sri Bahukelling (Buletin Ekonomi Perikanan, 2004)
Advertisement of fisheries products that showed on television constitute as communication tool among producers and consumers of its product. Housewifes are purchasers of some family's products. Housewifes have opportunity to access information and advertisement from television. Thus, it is crucial to assess the effectivity of the advertisement communication.The purposes of this research are 1) to identify the characteristics .of household's mothers in Kelurahan Lubang Buaya that related to decision of purchasing of fisheries products, 2) to identify the effectivity of advertisement communication by television for fisheries products includes: agar-agar powder with a trademark Swallow Globe, jelly powder with a trademark Nutrijell, jelly with a trademark Okky Jelly, Sardine canned with a trademark ABC, Fried Mackarel with a trademark Gaga, and 3) to found out the correlation of the effectivity of advertisement communication and the decision purchasing of fisheries products.The results of this research indicate that characteristics of households mother in Kelurahan Lubang Buaya are vary. The increasingly score of effectivity of advertisement communication having potency as more effective advertisement. The first rating of the effectivity of advertisement communication is agar-agar powder with a trademark Swallow Globe. The second is jelly powder with brand Nutrijell. The third is Fried Mackarel with brand Gaga. The fourth is Sardine canned with brand ABC and the fifth is jelly with a brand Okky Jelly. The statistical analysis indicate that the correlation between the effectivity (of advertisement communication and the purchasment decision for jelly powder with a brand Nutrijell is not significant at 98 % level of significance. However the correlation are Significant at 98 % level of sigficance for agar-agar powder with a trademark Swallow Globe, jelly with a trademark swallow Okky Jelly, Sardine canned with a trademark ABC and Fried Mackarel with a trademark Gaga.